A Low Cost Hardware and Software Platform for Biomedical Signal Acquisition and Treatment - Satiro, João Victor Melquiades; Cruz, Ianny Andrade; Prudente, Fabio; Santana, Danyelle; Lisboa , Edson (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
The correct measurement and processing of human biopotentials has been helping the medical sciences in the diagnosis of the most diverse pathologies. For many years the measurement of biopotentials has attracted great interest from the academic / scientific and industrial communities; with the technological evolution, several platforms models, with several functionalities, are available. However, the proposed solutions are generally proprietary, which generates total dependence on the solutions adopted and are, in general, limited because they are patented technology. Given this scenario, the present work proposes an integrated low-cost architecture of hardware and software that allows the measurement and treatment of different biomedical signals. The proposed approach is based on dedicated integrated circuits and passive components for the hardware module, connected to a programmable module, based on Arduino technology with direct communication to the computer in an interactive supervisory system.